NSC746364, a G-Quadruplex-Stabilizing Agent, Suppresses Cell Growth of A549 Human Lung Cancer Cells Through Activation of the ATR/Chk1-Dependent Pathway - Yun-Lung Chung; Chun-Hsu Pan; Wei-Hung Liou; Ming-Jyh Sheu; Wen-Hsin Lin; Tsung-Chih Chen; Hsu-Shan Huang; Chieh-Hsi Wu (Elsevier, 2014)
Abstract.: The telomere is considered to be a potential target for cancer therapy. NSC746364, a novel G-quadruplex-stabilizing agent, has been found to have cytotoxic effects on various cancer cells. To date, its pharmacological mechanisms are still unknown. The goal of this study was to investigate the molecular mechanisms of NSC746364 on the A549 human lung adenocarcinoma cell line. For this, we used a wide variety of in vitro assays. The intracellular signaling pathways including DNA damage sensing and response proteins, cell cycle regulatory proteins, and some key executors involved in apoptosis were evaluated in this study. Our study suggested that NSC746364 induced cell cycle arrest at the G2/M phase and triggers programing cell death on A549 human lung cancer cells, whose effects are modulated through the activation of the ATR/Chk1 pathway, the downregulation of cyclin B1 expression, and the activation of caspase-3. Consequently, our results indicated that NSC746364 may have therapeutic potential as a chemotherapy for non-small-cell lung cancers. Keywords:: NSC746364, non-small-cell lung cancer, G-quadruplex-stabilizing agent